The Influence of Entrepreneurship Education and Industrial Work Practices on Interest in Entrepreneurship in State Vocational High School Students in the Central Jakarta Region - Grace Yulianti; M Chaidir; Ngadi Permana (Jurnal Ad'ministrare, 2022)
This study aims to determine the effect of Entrepreneurship Education and Industrial Work Practices on Entrepreneurial Interests of State Vocational High School Students in the Central Jakarta Region. The research sample was 294 school students at 5 State Vocational Schools in Central Jakarta. Data collection was carried out through a survey method using a Google form which was distributed to the respondents. The collected data were then analyzed using multiple regression techniques using the E-views program. The results showed that entrepreneurship education and industrial work practices had a positive and significant effect on the interest in entrepreneurship at State Vocational High Schools in the Central Jakarta Region.